Giving Peace a Chance: Lessons From Translational Research in Colombia. - Casas, Andrés; Hameiri, Boaz (Peace & Conflict, 2021)
The current article is a personal account, describing the behind the scenes of an ongoing translational research project, initiated by Emile Bruneau in 2018, in collaboration with a team of scientists, filmmakers, and protagonists of the peace process in Colombia. The article is divided into two sections. The first section highlights the raising demand for the use of brain and behavioral sciences in program design and evaluation, especially to update and advance the area of peace and security. The second section reviews how we applied the three significant steps proposed by Moore-Berg et al. (2022) to carry out a research project faithful to the translational science approach in Colombia by (a) engaging with the communities involved to learn about the issues they face; (b) partnering with practitioners, to do research that will affect change in those communities; and (c) translating findings through different forms of engagement. Finally, we offer some concluding remarks about the advantages of adopting a Bruneau-ian approach to research.